2016
DOI: 10.1111/jai.13239
|View full text |Cite
|
Sign up to set email alerts
|

Status of knowledge of the Pallid Sturgeon (Scaphirhynchus albusForbes and Richardson, 1905)

Abstract: Summary The Pallid Sturgeon is listed as federally endangered under the Endangered Species Act in the United States. When the species was listed in 1990 it was considered extremely rare and was poorly understood. Habitat alteration, commercial harvest, environmental contaminants, and other factors were identified as threats. Today our scientific understanding of the species and its life history requirements have increased greatly as summarized below.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 86 publications
2
46
1
Order By: Relevance
“…The issue of senescence is rarely raised or approached in studies and reviews dealing with sturgeon and paddlefish ecology. Nevertheless, authors have reported or claimed either a lack of senescence or at least a lack of evidence of senescence in various sturgeon species such as white sturgeon ( Acipenser transmontanus ; Hildebrand et al., ), Gulf sturgeon ( A. oxyrinchus desotoi ; Sulak et al., ), and pallid sturgeon ( Scaphirhynchus albus ; Jordan et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The issue of senescence is rarely raised or approached in studies and reviews dealing with sturgeon and paddlefish ecology. Nevertheless, authors have reported or claimed either a lack of senescence or at least a lack of evidence of senescence in various sturgeon species such as white sturgeon ( Acipenser transmontanus ; Hildebrand et al., ), Gulf sturgeon ( A. oxyrinchus desotoi ; Sulak et al., ), and pallid sturgeon ( Scaphirhynchus albus ; Jordan et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Jordan et al () identifies the obstacles of collecting habitat data in a river as large and deep as the LMR with high discharge and fast current velocity. To evaluate selection for depth and current velocity, availability must be measured at a time concomitant with fish location.…”
Section: Discussionmentioning
confidence: 99%
“…Collection effort was distributed among the habitat types where sturgeon could be safely collected with trotlines, namely wing dike, secondary channel, sandbar, island tip, and natural bank (Table ). Pallid sturgeon and sympatric shovelnose sturgeon, Scaphirhynchus platorynchus (Rafinesque, 1,820), share morphological similarities throughout both species' ranges (Jordan et al, ). Recent studies document extensive hybridization between pallid sturgeon and shovelnose sturgeon in the LMR (Jordan et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pallid Sturgeon are benthic fish that are captured from a wide range of depths (Carlson and Pflieger ; Jordan et al. , ; Peters and Parham ; Herrala et al. ) and velocities (Snook et al.…”
mentioning
confidence: 99%